Mortality as a function of dust-haze in China: a multi-city time-series study. (October 2016) - Yang, Jun; Zhou, Maigeng; Yin, Peng; Li, Mengmeng; Ou, Chun-Quan; Gu, Shaohua; Liu, Qiyong
Abstract: Background: In recent years, hazardous dust-hazehas become one of the most catastrophic weather events in China. Reliable estimation of the burden of dust-haze on health has implications for implementation of mitigation measures. We did a time-series study to examine the health effects of dust-haze in China. Methods: A dust-haze day was defined ashaving daily visibility of less than 10 km, no rainfall, and relative humidity of less than 80%. A two-stage analysis was used to assess the effect of dust-haze on city-specific, cause-specific, sex-specific, and age-specific mortality in ten Chinese provincial capitals. Daily counts of deaths, further stratified by regions and individual characteristics, were obtained from the China Information System of Death Register and Report of the Chinese Center for Disease Control and Prevention; daily meteorological data were obtained from the China Meteorological Data Sharing Service System. A distributed lag model was applied to estimate the city-specific delayed effects of dust-haze on mortality, after controlling for long-term trend, seasonality, day ofthe week, and weather conditions. The maximum lag was set to 14 days for the lagged effects of dust-haze. The pooled effects across cities were then obtained using meta-analysis, based on restricted maximum likelihood estimation. This study was approved by the Ethics Committee of the Chinese Center for Disease Control and Prevention (no 201214). Findings: The average number of days with dust-haze was 67 days (SD 49) (18·36%) per year, ranging from 17 days (4·7%) in Guangzhou to 139 days (38·08%) in Hefei. Generally, the effects of dust-haze were immediate and limited to 7 days, with mortality displacement (harvesting effect) during lag 7–12 days. The relationships between dust-haze and mortality significantly varied by city (Cochrane's Q=40·725, I 2 =84·26% p<0·0001. The pooled relative risk of mortality associated with dust-haze over a lag time of 0–14 days was 1·05 (95%CI 1·01–1·09), 1·04(0·96–1·13), 1·03(0·98–1·09), and 1·15 (1·03–1·29) for non-accidental, respiratory, cardiovascular, and diabetes-related mortality, respectively. Significant effects of dust-haze were found among females compared with males (relative risk 1·07, 95% CI 1·02–1·14 vs 1·02, 0·98–1·06) and in people aged 75 years or above compared with younger people (1·05, 1·00–1·09 vs 1·03, 0·98–1·08). Interpretation: Dust-haze has considerable effects on mortality risk in various cities in China. This study strongly supports the need for effective measures to reduce air pollution, and protective actions for vulnerable populations, to reduce adverse effects. Funding: National Basic Research Program of China (973 Program) (Grant No 2012CB955504 ). C-Q Ou was supported by theNational Natural Science Foundation of China (81573249 ). No funding bodies had any role in study design, data collection and analysis, decision to publish, or preparation of the abstract.